A new era in the treatment of metabolic dysfunction-associated steatotic liver disease (MASLD): clinical breakthroughs and challenges - Zhifu You; Linglong Yang; Yuanhao Long; Dongye You; Qian Zhao (Frontiers in Pharmacology, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD), affecting nearly one-third of adults worldwide, encompasses a spectrum from steatosis to steatohepatitis (MASH), advanced fibrosis, cirrhosis, and hepatocellular carcinoma, with fibrosis stage as the primary determinant of liver-related outcomes and cardiovascular disease as the leading cause of mortality. Despite robust evidence that lifestyle interventions achieving ≥10% weight loss induce fibrosis regression in many patients, sustained success in routine practice remains elusive—realised in fewer than 15% of individuals—exposing a critical efficacy-effectiveness gap that demands pharmacologic therapy for those with clinically significant fibrosis. The period 2024–2026 has marked a transformative shift, with resmetirom (thyroid hormone receptor-β agonist) gaining accelerated approval in 2024 as the first agent to meet histologic endpoints in MASH, followed by semaglutide (GLP-1 receptor agonist) in 2025, both demonstrating substantial MASH resolution and fibrosis improvement in phase 3 trials; a diverse pipeline, including tirzepatide, efruxifermin, lanifibranor, denifanstat, and dual-incretin agonists, has yielded promising histologic and metabolic outcomes, with several advancing to phase 3 and updated guidelines endorsing pharmacotherapy for F2–F3 MASH, prioritising comorbidity-guided selection and synergy with lifestyle modification. Yet, these histologic gains must now be translated into reduced morbidity and mortality through an ambitious agenda of long-term outcome trials, precision biomarkers, and equitable, multidisciplinary care models.